Pulmonary volume-feedback and ventilatory pattern after bilateral lung transplantation using neurally adjusted ventilatory assist ventilation. (July 2021) - Grasselli, Giacomo; Castagna, Luigi; Abbruzzese, Chiara; Corcione, Nadia; Bottino, Nicola; Guzzardella, Amedeo; Colombo, Sebastiano Maria; Carlesso, Eleonora; Mauri, Tommaso; Rossetti, Valeria; Palleschi, Alessandro; Scaravilli, Vittorio; et al.
Abstract: Background: Bilateral lung transplantation results in pulmonary vagal denervation, which potentially alters respiratory drive, volume-feedback, and ventilatory pattern. We hypothesised that Neurally Adjusted Ventilatory Assist (NAVA) ventilation, which is driven by diaphragm electrical activity (EAdi), would reveal whether vagally mediated pulmonary-volume feedback is preserved in the early phases after bilateral lung transplantation. Methods: We prospectively studied bilateral lung transplant recipients within 48 h of surgery. Subjects were ventilated with NAVA and randomised to receive 3 ventilatory modes (baseline NAVA, 50%, and 150% of baseline NAVA values) and 2 PEEP levels (6 and 12 cm H2 O). We recorded airway pressure, flow, and EAdi. Results: We studied 30 subjects (37% female; age: 37 (27–56) yr), of whom 19 (63%) had stable EAdi. The baseline NAVA level was 0.6 (0.2–1.0) cm H2 O μV −1 . Tripling NAVA level increased the ventilatory peak pressure over PEEP by 6.3 (1.8), 7.6 (2.4), and 8.7 (3.2) cm H2 O, at 50%, 100%, and 150% of baseline NAVA level, respectively ( P <0.001). EAdi peak decreased by 10.1 (9.0), 9.5 (9.4) and 8.8 μV (8.7) ( P <0.001), accompanied by small increases in tidal volume, 8.3 (3.0), 8.7 (3.6), and 8.9 (3.3) ml kg −1 donor's predicted body weight at 50%, 100%, and 150% of baseline NAVA levels, respectively ( P <0.001). Doubling PEEP did not affect tidal volume. Conclusions: NAVA ventilation was feasible in the majority of patients during the early postoperative period after bilateral lung transplantation. Despite surgical vagotomy distal to the bronchial anastomoses, bilateral lung transplant recipients maintained an unmodified respiratory pattern in response to variations in ventilatory assistance and PEEP. Clinical trial registration: NCT03367221.